Efektivitas Metode Gambar dan Permainan dalam Meningkatkan Literasi Anak Panti: Suatu Kajian Mahasiswi Kesejahteraan Sosial FISIP USU - Sigalingging, Susanthio Theresia; Saragih, Mujahid Widian (Medan Resource Center, 2023)
This research aimed to enhance reading interest and reading culture among children at Fiber Permata Kasih orphanage. The research subjects were elementary school-aged children residing in the orphanage. The identified problem was the lack of reading culture among these children, leading to learning difficulties. This issue was exacerbated by the digitalization trend and the use of gadgets, which consumed the children's time for reading books. This research was an educational mini-project utilizing the social group work approach. The Delphi method was employed through Focus Group Discussions (FGD). The stages of social group work were carried out, ranging from the preparation to the termination phase. Activities were conducted in the form of interactive sessions using engaging picture and game methods to attract children's interest in reading. The research results demonstrated an increase in reading interest and reading culture among the orphanage children after participating in the activities. The children became more interested in reading and understood the importance of reading for their learning process at school. The implication of this research is the need to develop programs that promote the growth of reading culture among children from an early age, particularly for those living in orphanages